2019
DOI: 10.3390/en12132585
|View full text |Cite
|
Sign up to set email alerts
|

An Unsupervised Classification Method for Flame Image of Pulverized Coal Combustion Based on Convolutional Auto-Encoder and Hidden Markov Model

Abstract: Combustion condition monitoring is a fundamental and critical issue that needs to be addressed in the wide-load operation of coal-fired boilers. In this paper, an unsupervised classification framework based on the convolutional auto-encoder (CAE), the principal component analysis (PCA), and the hidden Markov model (HMM) is proposed to monitor the combustion condition with the uniformly spaced flame images, which are collected from the furnace combustion monitoring system. First, CAE is adopted to extract the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…One of the applications in which these networks perform particularly well is the detection of anomalies in the time series of different signals. 3236 In the study, we utilised three types of DRNNs. They are as follows: LSTM recurrent neural network, one-dimensional (1D) convolutional neural network LSTM (CNN-LSTM) and 1D convolutional LSTM (ConvLSTM).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the applications in which these networks perform particularly well is the detection of anomalies in the time series of different signals. 3236 In the study, we utilised three types of DRNNs. They are as follows: LSTM recurrent neural network, one-dimensional (1D) convolutional neural network LSTM (CNN-LSTM) and 1D convolutional LSTM (ConvLSTM).…”
Section: Methodsmentioning
confidence: 99%
“…Gangopadhyay et al 14 leveraged images from hi-speed flame videos as well as the sound pressure data for detecting instability in an experimental combustion system. Qiu et al 15 used uniformly spaced flame images in recognition of the pulverised coal (PC) combustion status (stable, semi-stable and unstable) in the thermal power plant. Liu et al 16 used a deep belief network to predict the oxygen content at the combustion system outlet.…”
Section: Introductionmentioning
confidence: 99%
“…A large number of existing studies have shown that deep learning-based classification method has good classification performance, and has achieved great success in computer vision, image processing and other fields. Some representative deep learning techniques include convolutional neural network (CNN) [9,10], recurrent neural network (RNN) [11,12], generative adversarial network [13,14] and convolutional auto-encoder [15,16]. Recently, a series of deep learning-based classification frameworks have been widely used in the field of remote sensing [17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Various architectures of such networks have been developed, and many of them achieve excellent performance in image recognition tasks, including flame images. Examples include deep convolutional neural networks [ 2 , 3 , 4 , 5 , 6 ], deep belief networks [ 7 , 8 ], deep convolutional auto-encoder [ 9 ], deep convolutional auto-encoder connected with the principal component analysis and the hidden Markov model [ 10 ], deep, fully connected neural networks [ 11 ], deep convolutional selective autoencoder [ 12 ] and various architectures followed by a symbolic time series analysis [ 13 , 14 ]. Each of the architectures mentioned above plays a vital role in a specific application area.…”
Section: Introductionmentioning
confidence: 99%